Developing and validating a nomogram for cognitive impairment in the older people based on the NHANES - Ma, Xiaoming; Huang, Wendie; Lu, Lijuan; Li, Hanqing; Ding, Jiahao; Sheng, Shiying; Liu, Meng; Yuan, Jie (Frontiers in Neuroscience, 2023)
Objective To use the United States National Health and Nutrition Examination Study (NHANES) to develop and validate a risk-prediction nomogram for cognitive impairment in people aged over 60 years. Methods A total of 2,802 participants (aged ≥ 60 years) from NHANES were analyzed. The least absolute shrinkage and selection operator (LASSO) regression model and multivariable logistic regression analysis were used for variable selection and model development. ROC-AUC, calibration curve, and decision curve analysis (DCA) were used to evaluate the nomogram’s performance. Results The nomogram included five predictors, namely sex, moderate activity, taste problem, age, and education. It demonstrated satisfying discrimination with a AUC of 0.744 (95% confidence interval, 0.696–0.791). The nomogram was well-calibrated according to the calibration curve. The DCA demonstrated that the nomogram was clinically useful. Conclusion The risk-prediction nomogram for cognitive impairment in people aged over 60 years was effective. All predictors included in this nomogram can be easily accessed from its’ user.